Tracking acute flaccid paralysis in Niger: a half-decade epidemiological portrait (2016–2021) - El Khalef Ishagh; Marc Talatou Ouédraogo; Batouré Oumarou; Mutenda Sheria Kaya; Gbaguidi Aichatou Diawara; Abdoulaye Macire Camara; Seyni Moussa; Kuyangisa Bienvenu; Joseph Toko; Hamidou Harouna; Haladou Moussa; N.’Zue Kofi; et al. (BMC Infectious Diseases)
Abstract Background Recently, a total of 74 circulating vaccine-derived poliovirus (cVDPV) outbreaks were detected in 39 countries, with 672 confirmed Acute Flaccid Paralysis (AFP) cases identified in 27 countries. Despite progress, Niger experienced cVDPV outbreaks in 2018, highlighting the importance of maintaining AFP surveillance as a tool for polio eradication. This analysis aims to comprehensively assess AFP surveillance trends, patterns, and challenges in Niger, offering insights for public health initiatives in conflict-affected contexts. Methods We analyzed nationwide AFP surveillance data from 2016 to 2021. The data included information about the person's background, vaccinations, medical history, cVDPV, AFP cases, stool samples, how quickly AFP cases were reported, how complete weekly zero reporting (WZR) was, and non-polio enteroviruses (NPEV). Tables, graphs, and maps presented the study findings. Results A total of 4,134 AFP cases under 15 years old were included, with a sex ratio of 1.3. Most cases (79.85%) were aged 1 to 4 years, and 79.44% received three or more doses of oral polio vaccine (OPV). Fever onset (90.13%), asymmetric paralysis (80.33%), and a 3-day AFP progression (80.48%) were common. cVDPV2 was found in 33 cases, predominantly in Zinder province. The annualized non-polio AFP rate per 100,000 population < 15 years fluctuated, with the lowest at 2.5 in 2016 and highest at 8.7 in 2018 (mean 5.93). Surveillance indicators, including faecal specimen collection, follow-up exams, NPEV detection, timeliness of AFP case notification, WZR, and timely laboratory results performed above the set target. However, stool specimen quality was suboptimal (69% in 2016), timeliness of AFP case investigation and contact sampling, and stool transportation times were below the set target. Five districts reported less than 80% stool adequacy. Conclusion This study underscores the importance of continued AFP surveillance in Niger, with room for improvement in stool specimen quality and transportation times. Enhancing these aspects can improve public health efforts in conflict-affected areas and contribute to polio eradication in the region.